2006
DOI: 10.1038/sj.ki.5000182
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and inflammation-associated cachexia in chronic kidney disease

Abstract: Leptin is an adipocyte-derived hormone that acts as a major regulator of food intake and energy homeostasis. It circulates both as a free and as a protein-bound entity. Leptin is released into the blood in proportion to the amount of body fat and exerts sustained inhibitory effects on food intake while increasing energy expenditure. The leptin receptor belongs to the class I cytokine receptor superfamily and possesses strong homology to the signal-transducing subunits of the IL-6 receptor. The hypothalamic mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(94 citation statements)
references
References 32 publications
2
84
0
8
Order By: Relevance
“…In humans with obesity, leptin levels may be inappropriately high due to hyporesponsiveness to leptin (35) but the levels decline rapidly during fasting (36). In patients with CKD, leptin is elevated due to decreased plasma clearance and increased production (37). A clinical study found normal plasma leptin levels prior to first dialysis in patients with AKI and no significant differences in leptin levels between survivors and nonsurvivors with AKI (38).…”
Section: Discussionmentioning
confidence: 99%
“…In humans with obesity, leptin levels may be inappropriately high due to hyporesponsiveness to leptin (35) but the levels decline rapidly during fasting (36). In patients with CKD, leptin is elevated due to decreased plasma clearance and increased production (37). A clinical study found normal plasma leptin levels prior to first dialysis in patients with AKI and no significant differences in leptin levels between survivors and nonsurvivors with AKI (38).…”
Section: Discussionmentioning
confidence: 99%
“…75,76 Levels of TNF-␣, a cytokine associated with cachexia, and cortisol, a stress hormone associated with depression and dysregulated carbohydrate metabolism, as well as other such mediators have also been shown to be elevated in ESRD patients treated with HD. 55,77,78 …”
Section: Malnutritionmentioning
confidence: 99%
“…Serum leptin levels are also known to be higher in patients who are undergoing PD, such as patients with hemolytic uremic syndrome, when compared with individuals with normal renal function. This observation may be caused by the filtering of leptin at the glomerulus without obstruction and the degradation of the protein in the renal tubules, as a result of the impaired clearance by the kidney (17,18). In addition, malnutrition is a dominant characteristic of uremic syndrome, and nutritional indicators, including the body mass index (BMI), the distribution of body fat and the plasma concentration of albumin, are known to be associated with the development of renal failure (19,20).…”
Section: Introductionmentioning
confidence: 99%